Towards The Development of a Protocol for Cryopreservation of Embryos of a Recalcitrant Seed (Artocarpus Heterophyllus Lam.) - Krishnapillay, Baskaran (1989)
Long term storage of recalcitrant seeds by conventional storage methods have by far been unsuccessful. In this study the excised embryos of seeds of jackfruit (Artocarpus heterophyllus). a recalcitrant species has been attempted at for long term preservation using cryogenic means. Stage of fruit maturity was critical in the study where embryos excised from mature unripe fruits were found to be the most appropriate. Selection of uniform sized embryos (4.0 - 5.0 m m in length) minimised variability in embryo fresh weight and moisture content to a considerable extent. A modified Murashige and Skoog medium containing 1.0 mg/l each of NAA and BAP, 2 gil of activated charcoal and 170 mg/l of NaH2 P04. H20 was found to be a suitable medium for development and growth of the excised jackfruit embryos. The safe critical moisture limit for excised jackfruit embryos was found to be around 14-15%. Storage of embryos dried to this moisture limit by conventional storage methods with a view to long term storage was unsuccessful. The maximum storage period achieved was only one month. Attempts at direct storage in liquid nitrogen after desiccation to near critical moisture limit was also found to be unsuccessful.